2015
DOI: 10.1248/bpb.b15-00480
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination Method of Epoxyeicosatrienoic Acids and Dihydroxyeicosatrienoic Acids by LC-MS/MS System

Abstract: Epoxyeicosatrienoic acids (EETs) are produced primarily by CYPs from arachidonic acid (AA) and then further metabolized to the corresponding dihydroxyeicosatrienoic acids (DHETs). EETs play important roles in physiological processes such as regulating vasodilation and inflammation. Thus, the drug inhibition of CYP-mediated AA metabolism could reduce production of EETs, potentially resulting in adverse cardiovascular events. The aim of this study was to develop a simple method to simultaneously determine the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Eicosanoids were determined by LC‐MS/MS as described in detail by Mukai et al . . All incubations were within the linear range of the AA metabolism with respect to the incubation duration and P450 content.…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Eicosanoids were determined by LC‐MS/MS as described in detail by Mukai et al . . All incubations were within the linear range of the AA metabolism with respect to the incubation duration and P450 content.…”
Section: Methodsmentioning
confidence: 54%
“…Incubation was performed using the method of Mukai et al . with some modifications. Each ARB stock solution was evaporated and reconstructed to create the final concentration (0, 10, 50, 100 and 500 μM) in the incubation medium.…”
Section: Methodsmentioning
confidence: 99%
“…18) An Agilent 1200 series (Santa Clara, CA, U.S.A.) LC system was used to separate samples. Separation was performed on an Ascentis Express C18 column measuring 100 mm ×2.1 mm with a particle size of 2.7 µm (Supelco, Sigma-Aldrich, St. Louis, MO, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
“…20,21) An Agilent 1200 series HPLC system (Santa Clara, CA, U.S.A.) was used with a binary pump, a degasser, and a thermostatic autosampler. HPLC separation was achieved using an Ascentis Express C18 column (10 cm×2.1 mm, 2.7 µm, Sigma-Aldrich).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…We previously developed a method for the simultaneous quantification of EETs and DHETs by LC-MS/MS. 20) Using this method, we demonstrated that several ARBs inhibit AA metabolism in recombinant CYP (rCYP) 2C8, 21) rCYP2C9, rCYP2J2, and HLMs 22) ; among the ARBs, telmisartan exhibited more potent inhibitory effect towards the CYP enzymes. 21,22) Several studies have revealed that telmisartan inhibits CYP2C9 23) and CYP2J2 24) in HLMs.…”
mentioning
confidence: 99%